Does the FIFA 11+ shoulder injury prevention program reduce the incidence of upper extremity injuries among soccer goalkeepers? A randomised controlled trial - Al Attar, W. S. A.; Alshehri, M. A. (British Journal of Sports Medicine, 2021)
Background: Goalkeepers appear to be the players who are at most risk of sustaining a shoulder injury. Many researchers have reported that goalkeepers are more likely, than outfield players, to injure their upper limb. The FIFA 11+S is structured according to the FIFA 11+ program which is already being successfully used to prevent injuries. Objective: To investigate the effectiveness of the FIFA 11+S in reducing the incidence of upper extremity injuries Design: Randomised controlled trial. Setting: Amateur soccer. Patients (or Participants): Male goalkeepers aged 14 to 35 years were randomly assigned to the experimental group (n = 360) or the control group (n =366). Interventions (or Assessment of Risk Factors): Experimental groups performed FIFA 11+S exercises for 20-25 minutes. The control group practiced their usual warm up. Main Outcome Measurements The incidence of upper extremity injuries, mechanism, type and severity of injury. Results: During one season, 50 injuries (0.62 injuries/1000 exposure hours) were reported in the experimental group and 122 injuries were reported in the control group (1.94 injuries/ 1000 hours). The FIFA 11+S significantly reduced the total number of upper extremity injuries (RR =0.42 [0.31-0.56]; p < 0.00001; Number Needed to Treat= 5.1), the incidence of contact injury (RR =0.39 [0.27-0.55]; p < 0.00001), the incidence of initial injury (RR =0.43 [0.31-0.59]; p < 0.00001) and the incidence of recurrent injury (RR =0.32 [0.12-0.86]; p < 0.05) more than the usual warm up. Minor injury severity (RR = 0.41 [0.29-0.58]; p < 0.00001) and moderate injury severity (RR = 0.44 [0.20-0.94]; p < 0.05) were significantly reduced in the experimental group (FIFA 11 +S) compared to the control group. Conclusions: This is the first study investigating the effectiveness of the FIFA 11+S in reducing the incidence of upper extremity injuries. This randomised trial provides evidence that implementation of the FIFA 11+S can reduce the incidence of upper extremity injuries among goalkeepers more than usual warm-up.